2001
DOI: 10.1038/modpathol.3880450
|View full text |Cite
|
Sign up to set email alerts
|

Angiotropic Lymphoma: An Immunophenotypically and Clinically Heterogeneous Lymphoma

Abstract: Angiotropic lymphoma (AL) is an uncommon lymphoma often presenting with nonspecific clinical features and having a high mortality rate. Although not specifically recognized by the Revised European-American Classification of Lymphoid Neoplasms, it likely will appear as a subtype of diffuse large B-cell lymphoma in the upcoming WHO classification. Some authors may also consider it to be a subtype of cutaneous lymphomas. Recent studies have reported an immunophenotypic heterogeneity of AL, and in rare instances, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
72
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(78 citation statements)
references
References 52 publications
(56 reference statements)
3
72
3
Order By: Relevance
“…In contrast to the previous report by Yegappan et al [8], EBV was detected in the lymphoma cells of our patient. It has been reported that DLBCL in immunocompromised patients are more frequently EBV + than sporadic DLBCL [12,13].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to the previous report by Yegappan et al [8], EBV was detected in the lymphoma cells of our patient. It has been reported that DLBCL in immunocompromised patients are more frequently EBV + than sporadic DLBCL [12,13].…”
Section: Discussioncontrasting
confidence: 99%
“…She had shown neither neurological abnormalities nor skin lesions, which are typically found in classical IVLBL [6][7][8], but she had also never shown the clinical features of Asian variant/B-LAHS [9,10]. Therefore, we diagnosed her as having classical IVLBL which originated in the uterus and was found incidentally at the time of hysterectomy for the huge myoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The survival of patients with CD5+DLBCLis significantly worse than that of patients with CD5" DLBCL. Moreover, several patients with CD5+ IVL have been described (17,18).…”
Section: Discussionmentioning
confidence: 99%